EPISTEMOLOGY IN COMPARATIVE THEOLOGY - Catherine Cornille (Perspectiva Teológica)
Comparative theology involves the systematic theological engagement with the teachings and practices of another religious tradition. This raises numerous epistemological questions, which may focus on the possibility of genuine understanding of other religions, on the status of truth in other religions, on the process of discernment of truth in those religions, and on the changes occurring in the contents of teachings and practices when transposed from one religious tradition into another. Addressing these questions requires engagement with the methods and approaches of religious studies, theology of religions, as well as critical engagement with examples of comparative theology. This article touches upon these questions by focusing on developments within Christian comparative theology.